2009
DOI: 10.1111/j.1468-1331.2008.02498.x
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter long‐term follow‐up of children with idiopathic West syndrome: ACTH versus vigabatrin

Abstract: Idiopathic WS with normal MRI is associated with a good cognitive outcome. Early ACTH treatment, administered within 1 month, yields a better cognitive and seizure outcome than vigabatrin or late ACTH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 19 publications
6
37
1
2
Order By: Relevance
“…In a Class III study, early treatment initiation (\1 month following onset of symptoms) in 102 children with cryptogenic spasms, led to improved neurodevelopmental outcome [48]. Favourable cognitive outcome with shorter interval to treatment (\3 weeks [108], \4 weeks [109] and \4 weeks [42]) has also been seen in recent studies including patients with both cryptogenic and symptomatic spasms.…”
Section: Tuberous Sclerosis (Ts)mentioning
confidence: 90%
See 1 more Smart Citation
“…In a Class III study, early treatment initiation (\1 month following onset of symptoms) in 102 children with cryptogenic spasms, led to improved neurodevelopmental outcome [48]. Favourable cognitive outcome with shorter interval to treatment (\3 weeks [108], \4 weeks [109] and \4 weeks [42]) has also been seen in recent studies including patients with both cryptogenic and symptomatic spasms.…”
Section: Tuberous Sclerosis (Ts)mentioning
confidence: 90%
“…In a multicentre retrospective study in Israel in children with idiopathic West syndrome [42] (Class IV), 14 children were treated with vigabatrin (100-180 mg/kg/day) and 14 with ACTH (100 IU on alternate days). Spasm cessation with vigabatrin at 2 weeks was 80 % and with ACTH was 88 %.…”
Section: Is Acth More Effective Than Vigabatrin For Shortterm Treatmementioning
confidence: 99%
“…On sekiz aydan sonra nadir görülmekle birlikte, başlangıcı 4 yaş kadar geç olan olgular bildirilmiş-tir [5]. Önceki çalışmalarla benzer şekilde [10][11][12][13], çalışmamızda başlangıç yaşı ortalama 6.23 aydı.…”
Section: Discussionunclassified
“…Belirtilerin başlangıcından tanıya kadar geçen süre gelişmiş ülkelerde 1-1.5 ay arasında bildirilirken [10,12,13], gelişmekte olan ülkelerde 7.9 ay kadar uzun olabilmektedir [11]. Çalışmamızda ise bu süre 1.36 aydı.…”
Section: Discussionunclassified
“…These treatments may stop IS in 60% -90% of cases, depending on etiology, but they do not necessarily prevent recurrences or persistence of other epileptic seizures or neurodevelopmental deficits. In WS of unknown etiology (old cryptogenic category), early cessation of spasms with hormonal therapy has been shown to partially improve neurodevelopmental outcomes (Riikonen 1982;Lombroso 1983;Kivity et al 2004;Lux et al 2005;Lux and Osborne 2006;Cohen-Sadan et al 2009;Darke et al 2010;O'Callaghan et al 2011), although no difference in outcome was reported in a different study (Mohamed et al 2011). The need for more effective and better-tolerated therapies with rapid onset of action is evident, including infants with IS caused by structural/metabolic etiologies who have poorer prognosis and treatment response.…”
Section: Animal Models Of Epileptic/is and West Syndromementioning
confidence: 99%